ABOUT THE IMPENDING DEMOGRAPHIC PIT AND A MORATORIUM ON THE REFORM OF THE NATIONAL HEALTH CARE - V. A. Alekseev; K. N. Borisov; I. V. Lin'kova (Модернизация, инновация, развитие, 2015)
Abstract. Despite the upbeat statements by politicians about positive changes in the lives of citizens, according to the WHO report on the health situation in Europe, a true picture of their wealth in the Eastern part of the region, which includes Russia, is far from blissful. The country is currently covered by an epidemic of reforms in all spheres of society. Particularly malignant character epidemic in health care reform is, clearly manifesting itself in a tendency of avoiding the constitutional right to an affordable, skilled and free medical care to the commercial side of medicine. The necessity of ads temporary moratorium on ineffective reforms in health care.